Matthew Flinders Senior (1751–1802): Surgeon and 'man midwife'. (May 2020) - Shields, Linda; Jomeen, Julie; Smyth, Wendy; Stanley, David
Until the eighteenth century, midwifery was the sole domain of women, but changes in medical science saw it appropriated by medical men and the 'man-midwife' emerged. This paper demonstrates the work of a man-midwife in a small English village in one year, 1775, using his accounts and correspondence. The man was Matthew Flinders Senior, 'surgeon and man-midwife' at Donington, Lincolnshire. He was the father of Captain Matthew Flinders, the famous navigator who mapped the coast line of Australia and who coined that name. Primary sources, published as a collection by the Lincoln Record Society, were used. Flinders Senior made a good living from his midwifery, charging rates commensurate with those charged by obstetricians today (with reduced costs for the poor). His descriptions of his practice show how midwifery was conducted in rural England during the development of medicine as a high-status profession. The paper uses data from one year to provide a snap shot of the work of a rural surgeon and man-midwife, but much more is available in the published collection, providing ready access for researchers who may like to pursue such work further.